2017
DOI: 10.1051/shsconf/20173300063
|View full text |Cite
|
Sign up to set email alerts
|

Portrayal of Women’s Images in Television Dramas: A Malaysian Case

Abstract: Abstract. Current situations brought about by globalisation and sophisticated innovations in new technology not only have created a new understanding of the world around us but also conscientiously sensitised society, particularly the women towards a more active role in shaping their world. An important contributory factor that can determine the success of women is their centrality in the media, through media positions held or through media images portrayed. What this paper has endeavoured to show is the portr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Content analysis from the Siri za familia series shows that the male gender is framed and presented as rational and competitive people who can make essential family decisions. This relates to the literature review from [11], who observed that women are always presented as irrational, sensitive, emotional, dependent, or indecisive. In contrast, men are always presented as rational, intelligent, independent, and competitive.…”
Section: Dominant Gender Frames Portrayed In Siri Za Familia Seriesmentioning
confidence: 89%
See 2 more Smart Citations
“…Content analysis from the Siri za familia series shows that the male gender is framed and presented as rational and competitive people who can make essential family decisions. This relates to the literature review from [11], who observed that women are always presented as irrational, sensitive, emotional, dependent, or indecisive. In contrast, men are always presented as rational, intelligent, independent, and competitive.…”
Section: Dominant Gender Frames Portrayed In Siri Za Familia Seriesmentioning
confidence: 89%
“…Although the representation of women in television drama series is currently better than before, women are always presented negatively through dialogues or actions. Women are always presented as irrational, sensitive, emotional, dependent, or indecisive, while men are always presented as rational, intelligent, independent, and competitive [11].…”
Section: Television and The Portrayal Of Gender Framesmentioning
confidence: 99%
See 1 more Smart Citation
“…Television dramas need a change of direction that portray women in different roles and represent women issues (Ibrahim et al, 2017). It is the need of hour to change the presentation of women portrayal in Pakistani television dramas (Huma Z. E, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%